2019
DOI: 10.1111/os.12569
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Particle Size Ratios on the Physical and Chemical Properties of Surgical‐Grade Calcium Sulfate Hemihydrate

Abstract: Objectives To analyze the optimum particle size or formula ratio of surgical‐grade calcium sulfate (CS) for appropriate compressive strength, setting time, and vitro degradation rate. Methods Three types of calcium sulfate hemihydrate (CSH) particles with diameters of 0–37.5 μm, 37.5–75 μm, and >75 μm were screened. Based on formulation ratio of different particles, this topic is divided into 10 groups by the unconstrained third‐order simplex lattice mixing design scheme in formula design experiment. The optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In a study by Hu et al, the authors studied the effect of particle size on the biophysical properties of CS bone grafts. 64 This group found that grafts comprised of smaller sized CS particles demonstrated increased compressive strength and a slower in vitro degradation rate. In this regard, various nano-sized bone grafting materials have received FDA approval in the past decade for osseous corrective surgeries.…”
Section: Nanocrystalline Csmentioning
confidence: 99%
“…In a study by Hu et al, the authors studied the effect of particle size on the biophysical properties of CS bone grafts. 64 This group found that grafts comprised of smaller sized CS particles demonstrated increased compressive strength and a slower in vitro degradation rate. In this regard, various nano-sized bone grafting materials have received FDA approval in the past decade for osseous corrective surgeries.…”
Section: Nanocrystalline Csmentioning
confidence: 99%
“…[2][3][4] As for the utilization of a-HH, in general, the larger the particle size and the higher the crystallinity, the better the performance of a-HH. [5][6][7] It is reported that the short columnar a-HH is an ideal crystal with high mechanical strength and good performance, [8][9][10][11] and additives are usually applied to modulate the crystal morphology of a-HH. In order to obtain short columnar a-HH, some special additives, such as citric acid, ethylenediamine tetracetic acid (EDTA), malic acid and aluminum chloride are used.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium sulfates are among the most used materials, and their applications include construction, food additives’ , targeted drug delivery, and plaster casts for medical and dental applications. , They are also used as resorbable bone repair materials. , …”
Section: Introductionmentioning
confidence: 99%